Clinical impact of lenvatinib in patients with unresectable hepatocellular carcinoma who received sorafenib - Yen-Yang Chen; Chih-Chi Wang; Yueh-Wei Liu; Wei-Feng Li; Yen-Hao Chen (PeerJ, 2020)
Background Lenvatinib has been approved for use in the systemic treatment for unresectable hepatocellular carcinoma (HCC). This study aimed to investigate the efficacy and safety of lenvatinib in patients with unresectable HCC who received sorafenib. Methods A total of 40 patients who received lenvatinib after sorafenib were retrospectively identified: as second line in 20 patients, third line in 10 patients, and fourth line and later lines in 10 patients. The treatment response to lenvatinib was determined in accordance with the guidelines of the modified Response Evaluation Criteria in Solid Tumors (mRECIST) every 2–3 months after commencement of lenvatinib. Results Median progression-free survival (PFS) and median overall survival (OS) of the whole population were 3.3 and 9.8 months, respectively. The objective response rate was 27.5%. Univariate and multivariate analyses showed that alpha-fetoprotein level >400 ng/mL was an independent prognostic factor of worse PFS and OS. The clinical outcomes of lenvatinib therapy as second-line, third-line, or fourth line and later line treatment were similar, and previous response to sorafenib could predict the response to subsequent lenvatinib. Most adverse events were grades 1–2, and the majority of patients tolerated the side effects. Our study confirms the efficacy and safety of lenvatinib as second-line and later line treatment for patients with unresectable HCC who received sorafenib in clinical practice.